2009
DOI: 10.1021/nn8008273
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Conjugation of Peptides onto Gold Nanoparticles Enhances Macrophage Response

Abstract: Murine bone marrow macrophages were able to recognize gold nanoparticle peptide conjugates, while peptides or nanoparticles alone were not recognized. Consequently, in the presence of conjugates, macrophage proliferation was stopped and pro-inflammatory cytokines such as TNF-alpha, IL-1beta, and IL-6, as well as nitric oxide synthase (NOS2) were induced. Furthermore, macrophage activation by gold nanoparticles conjugated to different peptides appeared to be rather independent of peptide length and polarity, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 38 publications
7
125
2
Order By: Relevance
“…Furthermore, ligand exchange has also been demonstrated with dendrimers Kim et al 2005d) and thiol-containing peptides in the case of gold nanoparticles (Levy et al 2004;Nativo et al 2008;Bastus et al 2009), and as well with proteins binding to quantum dots by replacing MAA on the surface (Gao et al 2002). The same principles also apply to Au rods, where the replacement of the cetyltrimethylammonium bromide (CTAB) double layer by thiol-containing PEG has been reported (Niidome et al 2006;Pierrat et al 2007).…”
Section: (C) Ligand Exchangementioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, ligand exchange has also been demonstrated with dendrimers Kim et al 2005d) and thiol-containing peptides in the case of gold nanoparticles (Levy et al 2004;Nativo et al 2008;Bastus et al 2009), and as well with proteins binding to quantum dots by replacing MAA on the surface (Gao et al 2002). The same principles also apply to Au rods, where the replacement of the cetyltrimethylammonium bromide (CTAB) double layer by thiol-containing PEG has been reported (Niidome et al 2006;Pierrat et al 2007).…”
Section: (C) Ligand Exchangementioning
confidence: 92%
“…In addition, examples for particle synthesis (Slocik et al 2005) and phase transfer (Euliss et al 2003) with the help of peptides have been reported. Making use of the biological functionality of certain peptides, the specific uptake of nanoparticles by cells can be optimized by conjugation of nanoparticles with the corresponding peptide, as reported for Au nanoparticles Liu et al 2007b;Nativo et al 2008) or quantum dots (Pinaud et al 2004) by ligand exchange with cysteine-containing peptides, as well as the reaction of the immune system towards nanoparticles may be modulated by the peptide coating (Bastus et al 2009). Also, coating of quantum dots with lipids pre-modified with e.g.…”
Section: (Iii) Peptides Proteins Enzymes and Antibodiesmentioning
confidence: 99%
“…To confirm the exchange of the capping agent for the three peptides, XPS analysis of the NPs was performed, showing the presence of Au and S. The binding energies measured (84.0 and 87.7 eV for Au 4f7/2 and 4f5/2, respectively, and 162 eV for S2p) are typical of AuNPs with thiolate capping agents [32]. Relative atomic amounts of sulfur (CALNN: 3.93%; CALND: 6.69%; CALNS 3.08%) and Au (CALNN: 89.3%; CALND: 89.2%; CALNS 89.1%) are within the range usually observed for AuNPs with thiolate capping agents.…”
Section: Synthesis and Characterization Of Aunpsmentioning
confidence: 99%
“…In biomedicine, INPs have to be functionalized in order to selectively interact with biological targets. For this purpose, they are usually coated with biological molecules such as antibodies (Wang et al, 2002;El-Sayed et al, 2005), aptamers (Farokhzad et al, 2006), peptides (Kogan et al, 2006;Bastús et al, 2009), and oligonucleotides (Rosi et al, 2006). Some relevant examples are the functionalization of INPs with uptake ligands that specifically bind to receptors of the cell membrane (ex.…”
Section: Surface Chemistry and Functionalizationmentioning
confidence: 99%
“…They can eventually be accidental. One interesting case is the modification of INP's surface when exposed to biological fluids and their non-specific binding of media proteins (Bastús et al, 2009). This is the case of loosely coated INPs, such as citrate-stabilized Au NPs, where citrate molecules are immediately replaced by media proteins.…”
Section: Surface Chemistry and Protein Coronamentioning
confidence: 99%